Using music to influence cognitive and affective responses in queues of low and high crowd density - Oakes, S.; North, Adrian (Routledge, 2008)
Within the context of an undergraduate registration queue, this study confirmed perceived wait duration to be a significant, positive function of the tempo of background music, and a significant, negative function of musical liking. In addition, it identified how the presence of music significantly reduced mean perceived duration estimates. Slow-tempo music produced significantly more positive affective responses than fast-tempo music in terms of satisfaction, relaxation, and positive disconfirmation of expectations of wait duration. The presence of music enhanced positive affective response with low crowd density, but diminished it with high crowd density. Musical liking significantly enhanced positive affective responses.